Nano-CMOS gate dielectric engineering - Wong, Hei (CRC Press, 2012)
This book is a systematic review of high-K gate dielectric materials for CMOS chips (complementary metaloxide semiconductors), which are used in image sensors and data convertors (amplifiers, digital camera sensors, etc). Scaling CMOS devices down to the nanoscale creates new materials challenges, and one effective response is to introduce novel materials such as High K dielectrics. The book presents the fundamental physics and properties of High-K materials and how they can be fabricated and used in Nano CMOS device - See more at: http://www.betterworldbooks.com/nano-cmos-gate-dielectric-engineering-id-1439849595.aspx&utm_source=Affiliate&utm_campaign=Text&utm_medium=booklink&utm_term=3630151&utm_content=Homepage#sthash.mhf9DArw.dpuf